PENANGGULANGAN BANJIR DI JAKARTA: EVALUASI KEBIJAKAN PEMERINTAH DAN SOLUSI BERKELANJUTAN - Jelibseda, Jelibseda; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Jakarta faces significant challenges in flood management due to rapid urbanization, climate change, and inadequate drainage systems. The government has implemented various policies, such as levee construction, river revitalization, and polder systems, yet their effectiveness remains debatable. This study aims to evaluate the implemented flood management policies and propose sustainable solutions. The research employs a qualitative approach with policy analysis based on secondary data from government reports, scientific journals, and expert interviews. The findings indicate that existing policies have not been fully effective in reducing flood risks due to a lack of inter-agency coordination, budget constraints, and low community participation. Therefore, sustainable solutions, including ecosystem-based approaches, improved green infrastructure, and technology integration in early warning systems, are essential to enhance urban flood resilience.